Penggunaan Abreviasi Bahasa Indonesia Dalam Komunikasi Elektronik Mahasiswa Pendidikan Manajemen Perkantoran Universitas Pendidikan Indonesia - Dharmawan, Aprillia Rossa; Sonia, Mia; Ardana, Reva Tirta; Azmi, Salma Afina; Rahayu, Shantika; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the phenomenon that often arises related to the increasing use of abreviation in electronic communication in the UPI Office Management Education student environment, starting from how abreviation is used and how much student knowledge about abreviation itself. The method used is a qualitative research approach method where each student has diverse views on the use of abreviation, this research data is collected through interviews which are then analyzed according to theory. The results of this study show that office management education students use abreviation in electronic communication, thus facilitating effective communication. The use of this abreviation can lead to misunderstandings in interpreting the meaning of the word conveyed to the recipient of the message. By using the right abreviation, office management education students can minimize the mismeaning and purpose of abreviation. It can be concluded from this study that office management education students are proven to use abreviation still often in electronic communication for the reason of facilitating information and speeding up the communication process